The Domino Effect: Nucleosome Dynamics and the Regulation of Base Excision Repair Enzymes - Julia C. Cook; Sarah Delaney (DNA, 2022)
DNA damage is induced by exogenous and endogenous sources, creating a variety of lesions. However, the cellular repair machinery that addresses and corrects this damage must contend with the fact that genomic DNA is sequestered in the nucleoprotein complex of chromatin. As the minimal unit of DNA compaction, the nucleosome core particle (NCP) is a major determinant of repair and poses unique barriers to DNA accessibility. This review outlines how the base excision repair (BER) pathway is modulated by the NCP and describes the structural and dynamic factors that influence the ability of BER enzymes to find and repair damage. Structural characteristics of the NCP such as nucleobase positioning and occupancy will be explored along with factors that impact the dynamic nature of NCPs to increase mobilization of nucleosomal DNA. We will discuss how altering the dynamics of NCPs initiates a domino effect that results in the regulation of BER enzymes.